LOP Game Development to Improve Early Childhood Mathematical-Logic Learning Ability - Wati, Epritha Kurnia; Wulansari, Widi (JPI (Jurnal Pendidikan Indonesia), 2021)
This study aims to develop a learning media product, namely the LoP Game to improve the Mathematical-Logic Learning Ability of Early Childhood Beginning. This type of research is a Research and Development (R&D) using a model developed by Borg and Gall. There are 3 stages used in this study from 10 stages proposed by Borg and Gall. These stages include: research and information collecting, planning, and develop preliminary form of product. Data validity analysis was performed using the Aiken formula. The data is obtained from the results of the instrument assessment in the form of a questionnaire from material experts and media experts. The feasibility assessment is tested by 3 material experts and 3 media experts. From the results of the validity test, it can be seen that the expert judgment for the media in the LoP game is all valid with all aspects that have been previously described. Thus, it can be said that the LoP game is appropriate and suitable for the development of early childhood abilities, especially mathematical-logic abilities.